2016
DOI: 10.1038/srep35859
|View full text |Cite
|
Sign up to set email alerts
|

Altered mitochondrial DNA copy number contributes to human cancer risk: evidence from an updated meta-analysis

Abstract: Accumulating epidemiological evidence indicates that the quantitative changes in human mitochondrial DNA (mtDNA) copy number could affect the genetic susceptibility of malignancies in a tumor-specific manner, but the results are still elusive. To provide a more precise estimation on the association between mtDNA copy number and risk of diverse malignancies, a meta-analysis was conducted by calculating the pooled odds ratios (OR) and the 95% confidence intervals (95% CI). A total of 36 case-control studies invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 69 publications
(70 reference statements)
4
68
1
1
Order By: Relevance
“…The combinations of the ingredients are altered according to individual preferences and it is preferred to be consumed in combination with zarda and gutkha. [33][34][35] The habit of betel quid chewing, cigarette smoking, gutkha, 36 zarda, 37 Khaini (chewing tobacco with lime), 38 alcohol along with cigarette smoking, and closed kitchen setup (minimal ventilation) with the use of traditional firewood for cooking are considered to be one of the potential risk factors responsible for HNSCC. 39 Tobacco consumption by cigarette smoking as well as chewing is also considered in development of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The combinations of the ingredients are altered according to individual preferences and it is preferred to be consumed in combination with zarda and gutkha. [33][34][35] The habit of betel quid chewing, cigarette smoking, gutkha, 36 zarda, 37 Khaini (chewing tobacco with lime), 38 alcohol along with cigarette smoking, and closed kitchen setup (minimal ventilation) with the use of traditional firewood for cooking are considered to be one of the potential risk factors responsible for HNSCC. 39 Tobacco consumption by cigarette smoking as well as chewing is also considered in development of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprograming is one of the key hallmarks of cancer (Ward and Thompson 2012), and mtDNA copy number has been reported to correlate with cancer invasiveness and overall patient outcomes (Chen et al 2016;Hu et al 2016). In addition, it has been suggested that lower levels of mtDNA in certain cancers may reflect a more stem-like metabolic program and be important in cancer stem cell biology (Lee et al 2015;Menendez 2015).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The relative quantifications employed by most mtDNA investigations make comparisons between different studies difficult to interpret, often producing conflicting results. Additionally, both PCR efficiency (Regier and Frey 2010;Hu et al 2016) and the manner in which DNA is isolated (Andreu et al 2009;Malik et al 2011) present hurdles to understand the roles of mtDNA copy number during aging and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprograming is one of the key hallmark of cancer (Ward and Thompson 2012) and mtDNA copy number has been reported to correlate with cancer invasiveness and overall patient outcomes (Chen et al 2016;Hu et al 2016). In addition, it has been suggested that lower levels of mtDNA in certain cancers may reflect a more stem-like metabolic program and be important in cancer stem cell biology (Lee et al 2015;Menendez 2015).…”
Section: Detection Of Mtdna In a Variety Of Human Cells By Ddmdmmentioning
confidence: 99%